2010
DOI: 10.1038/ncb2096
|View full text |Cite
|
Sign up to set email alerts
|

Control of endothelial sprouting by a Tel–CtBP complex

Abstract: We show that the transcriptional repressor Tel plays an evolutionarily conserved role in angiogenesis: it is indispensable for the sprouting of human endothelial cells and for normal development of the Danio rerio blood circulatory system. Tel orchestrates endothelial sprouting by binding to the generic co-repressor, CtBP. The Tel-CtBP complex temporally restricts a VEGF (vascular endothelial growth factor)-mediated pulse of dll4 expression and thereby directly links VEGF receptor intracellular signalling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…Previous studies identified a role for another ETS factor, TEL (ETV6), in the repression, rather than the activation, of DLL4 (Roukens et al, 2010). In this case, TEL bound to the DLL4 promoter under basal conditions to recruit a co-repressor protein, CTBP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified a role for another ETS factor, TEL (ETV6), in the repression, rather than the activation, of DLL4 (Roukens et al, 2010). In this case, TEL bound to the DLL4 promoter under basal conditions to recruit a co-repressor protein, CTBP.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional system have been developed to study sprouting angiogenesis in vitro, for example, endothelial sprouting from a planar endothelium into bulk collagen gel (24), lateral endothelial sprouting into a collagen gel isolated between two microfluidic channels formed in PDMS silicone (25), and 3D endothelial sprouting from microbead supports in a bulk gel (26). None of these systems allows for the initiation of angiogenesis from native-like vessels with luminal flow and simultaneous control of the chemical and cellular microenvironment of the endothelium.…”
Section: Resultsmentioning
confidence: 99%
“…Results indicate that KROX (a component of the early growth response genes [EGR] family) regulates a significant amount of the genes whose methylation status correlates with blood flow, capillary density, and arteriole counts (418, 1979, and 369, respectively). 14,15 Moreover, 536 genes associated with blood flow, 2805 genes associated with capillary density, and 460 genes associated with arteriole counts are regulated by MYCassociated zinc finger protein (MAZ), which is involved in cell proliferation and mediates vascular endothelial growth factor (VEGF)-induced angiogenesis. 16 Hence, interference of DNA methylation with KROX/EGR1 and MAZ might result in large effects on gene transcription and possibly on promotion of tissue repair by SV-APCs.…”
Section: Correlation Between Dna Methylation Profile Of Sv-apcs and Pmentioning
confidence: 99%